Prognostic role of carcinoembryonic antigen and carbohydrate antigen 19-9 in metastatic colorectal cancer: a BRAF-mutant subset with high CA 19-9 level and poor outcome - Thomsen, Maria (Br J Cancer, 2018)
BACKGROUND: Mutation status of RAS and BRAF, as well as serum levels of carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA 19-9), are biomarkers used in clinical management of patients with gastrointestinal cancers. This study aimed to examine the prognostic role of these biomarkers in a patient population that started first-line chemotherapy for unresectable metastatic colorectal cancer (mCRC) in the NORDIC-VII study. METHODS: CEA and CA 19-9 were measured in serum samples from 545 patients obtained before the start of chemotherapy. Four hundred and ninety-four patients had detectable levels of carbohydrate antigen 19-9 (CA 19-9). RAS (exons 2–4) and BRAF (V600E) mutation status were available from 440 patients. Overall survival (OS) was estimated in patient groups defined by serum CEA or CA 19-9 levels using cut-off values of 5 µg/L and 35 kU/L, respectively, in the total population and in subgroups according to RAS and BRAF mutation status. RESULTS: For both CEA and CA 19-9, elevated serum levels were associated with reduced OS in adjusted analyses which included RAS and BRAF mutation status, baseline World Health Organization performance status, and levels of alkaline phosphatase and C-reactive protein. The negative prognostic information provided by an elevated CA 19-9 level was particularly marked in patients with BRAF mutation (hazard ratio = 4.35, interaction P = 0.003, in an adjusted model for OS). CONCLUSIONS: High baseline serum concentrations of CEA and CA 19-9 provide independent information of impaired prognosis in mCRC. In patients with BRAF-mutant tumours, elevated serum CA 19-9 may identify a subgroup with highly aggressive disease and could contribute to improving therapeutic decisions.